Loneliness and phubbing in peruvian university students: the mediating role of the fear of missing out - Correa-Rojas, Jossué (2025)
Introduction: The main objective of the present research was to determine the effect of loneliness on Phubbing when Fear of Missing Out (FoMO) mediates this relationship. Method: The design is explanatory of latent variables, and three scales (Loneliness Scale, Fear of Missing Out Scale, and Phubbing Scale) were applied to a sample of 405 university students from two private universities in Metropolitan Lima. Results: It was found that there is an indirect, statistically significant effect of loneliness on Phubbing, through FoMO. Also, the total effect of the model was statistically significant. Furthermore, the independent variable (loneliness) significantly explains FoMO, and the mediating variable (FoMO) predicts Phubbing. Conclusions: Loneliness has an indirect effect on Phubbing through FoMO, implying that loneliness does not directly predict Phubbing, but when a person experiences fear of missing out, the effect of loneliness becomes relevant for the development of Phubbing.